Analisis Fenomena Kehilangan Air Sungai Cisuwarna - Petrus Syariman; Hendarmawan Hendarmawan (JURNAL TEKNIK HIDRAULIK, 2010)
Discharge from Cisuwarna River isone of the main inflows to Rawa Danau highly expected by local peopleeither upstream or downstream.Part of water loss of Cisuwarna caused not optimum domestic water use.Water loss indication can be seen from the simulation results by using SSARR model that calculateddischarge greater than observed.The methods used for water loss analysis are simultaneous dischargemeasurement, rainfall runoffand coefficient correlation analysis, and geological map interpretation.Theanalysis result has proven that the average water loss at Cisuwarna is about 12 .4 million cumec per year orabout 45% of calculated discharge.Water loss is assumedto flow into the fault before flowing into rawaDanau.Waterdeficitisalwaysgoingthrough everyyearinRawaDanau.